Fluoride‑induced hepatotoxicity is prevented by L‑Arginine supplementation via suppression of oxidative stress and stimulation of nitric oxide production in rats (2021)
Objective Concerns over fluoride toxicity have increased in recent times due to high exposures from various anthropogenic sources such as industrial sites, fluoride-containing pesticides, drugs, dental products, refridgerants and fire extinguishers. There is, therefore, continued search for agents that could ameliorate the toxicity of this chemical in various body organs. In this study, we sought to investigate the protective effects of L-Arginine (L-Arg), a nitric oxide donor, on liver toxicity induced by sodium fluoride (NaF) in rats. Methods Rats received NaF (300 mg L−1) in drinking water alone or in co-treatment with L-Arg at two different doses, 100 and 200 mg kg−1, by oral gavage, for 7 days. Markers of hepatotoxicity, oxidative stress and antioxidant status were thereafter assessed. Results NaF caused marked increase in serum transaminases: alanine aminotransferase, Aspartate aminotransferase and Alkaline phosphatase, along with atrophy of the centri-lobular hepatic cords and dilatation of the sinusoids. Moreover, NaF stimulated increases in hepatic contents of hydrogen peroxide (H2O2), nitric oxide (NO), protein carbonyls, malondialdehyde and advanced oxidation protein products. NaF also inhibited the activities of antioxidant enzymes, Glutathione peroxidase and Superoxide dismutase. However, L-Arg supplementation caused significant alleviation of NaF hepatotoxicity by reducing lipid and protein oxidation indices, stimulation of antioxidant systems along with increased production of NO. Conclusions L-Arg showed promise as a potential protective agent against NaF-induced hepatotoxicity via restoration of oxidant-antioxidant balance. Further studies are required to understand the involvement of NO signaling in the protective effects of L-Arg against fluoride toxicity.